5.9.18 Problems 1701 to 1800

Table 5.663: First order ode linear in derivative

#

ODE

Mathematica

Maple

4694

\[ {}y^{\prime }+\left (\tan \left (x \right )+y^{2} \sec \left (x \right )\right ) y = 0 \]

4695

\[ {}y^{\prime }+y^{3} \sec \left (x \right ) \tan \left (x \right ) = 0 \]

4696

\[ {}y^{\prime } = \operatorname {f0} \left (x \right )+\operatorname {f1} \left (x \right ) y+\operatorname {f2} \left (x \right ) y^{2}+\operatorname {f3} \left (x \right ) y^{3} \]

4697

\[ {}y^{\prime } = a \,x^{\frac {n}{1-n}}+b y^{n} \]

4698

\[ {}y^{\prime } = f \left (x \right ) y+g \left (x \right ) y^{k} \]

4699

\[ {}y^{\prime } = f \left (x \right )+g \left (x \right ) y+h \left (x \right ) y^{n} \]

4700

\[ {}y^{\prime } = \sqrt {{| y|}} \]

4701

\[ {}y^{\prime } = a +b y+\sqrt {\operatorname {A0} +\operatorname {B0} y} \]

4702

\[ {}y^{\prime } = a x +b \sqrt {y} \]

4703

\[ {}y^{\prime }+x^{3} = x \sqrt {x^{4}+4 y} \]

4704

\[ {}y^{\prime }+2 y \left (1-x \sqrt {y}\right ) = 0 \]

4705

\[ {}y^{\prime } = \sqrt {a +b y^{2}} \]

4706

\[ {}y^{\prime } = y \sqrt {a +b y} \]

4707

\[ {}y^{\prime }+\left (f \left (x \right )-y\right ) g \left (x \right ) \sqrt {\left (y-a \right ) \left (y-b \right )} = 0 \]

4708

\[ {}y^{\prime } = \sqrt {X Y} \]

4709

\[ {}y^{\prime } = \cos \left (x \right )^{2} \cos \left (y\right ) \]

4710

\[ {}y^{\prime } = \sec \left (x \right )^{2} \cot \left (y\right ) \cos \left (y\right ) \]

4711

\[ {}y^{\prime } = a +b \cos \left (A x +B y\right ) \]

4712

\[ {}y^{\prime }+f \left (x \right )+g \left (x \right ) \sin \left (a y\right )+h \left (x \right ) \cos \left (a y\right ) = 0 \]

4713

\[ {}y^{\prime } = a +b \cos \left (y\right ) \]

4714

\[ {}y^{\prime }+x \left (\sin \left (2 y\right )-x^{2} \cos \left (y\right )^{2}\right ) = 0 \]

4715

\[ {}y^{\prime }+\tan \left (x \right ) \sec \left (x \right ) \cos \left (y\right )^{2} = 0 \]

4716

\[ {}y^{\prime } = \cot \left (x \right ) \cot \left (y\right ) \]

4717

\[ {}y^{\prime }+\cot \left (x \right ) \cot \left (y\right ) = 0 \]

4718

\[ {}y^{\prime } = \sin \left (x \right ) \left (\csc \left (y\right )-\cot \left (y\right )\right ) \]

4719

\[ {}y^{\prime } = \tan \left (x \right ) \cot \left (y\right ) \]

4720

\[ {}y^{\prime }+\tan \left (x \right ) \cot \left (y\right ) = 0 \]

4721

\[ {}y^{\prime }+\sin \left (2 x \right ) \csc \left (2 y\right ) = 0 \]

4722

\[ {}y^{\prime } = \tan \left (x \right ) \left (\tan \left (y\right )+\sec \left (x \right ) \sec \left (y\right )\right ) \]

4723

\[ {}y^{\prime } = \cos \left (x \right ) \sec \left (y\right )^{2} \]

4724

\[ {}y^{\prime } = \sec \left (x \right )^{2} \sec \left (y\right )^{3} \]

4725

\[ {}y^{\prime } = a +b \sin \left (y\right ) \]

4726

\[ {}y^{\prime } = \left (1+\cos \left (x \right ) \sin \left (y\right )\right ) \tan \left (y\right ) \]

4727

\[ {}y^{\prime }+\csc \left (2 x \right ) \sin \left (2 y\right ) = 0 \]

4728

\[ {}y^{\prime }+f \left (x \right )+g \left (x \right ) \tan \left (y\right ) = 0 \]

4729

\[ {}y^{\prime } = \sqrt {a +b \cos \left (y\right )} \]

4730

\[ {}y^{\prime } = {\mathrm e}^{y}+x \]

4731

\[ {}y^{\prime } = {\mathrm e}^{x +y} \]

4732

\[ {}y^{\prime } = {\mathrm e}^{x} \left (a +b \,{\mathrm e}^{-y}\right ) \]

4733

\[ {}y \ln \left (x \right ) \ln \left (y\right )+y^{\prime } = 0 \]

4734

\[ {}y^{\prime } = x^{m -1} y^{1-n} f \left (a \,x^{m}+b y^{n}\right ) \]

4735

\[ {}y^{\prime } = a f \left (y\right ) \]

4736

\[ {}y^{\prime } = f \left (a +b x +c y\right ) \]

4737

\[ {}y^{\prime } = f \left (x \right ) g \left (y\right ) \]

4738

\[ {}y^{\prime } = \sec \left (x \right )^{2}+y \sec \left (x \right ) \operatorname {Csx} \left (x \right ) \]

4739

\[ {}2 y^{\prime } = 2 \sin \left (y\right )^{2} \tan \left (y\right )-x \sin \left (2 y\right ) \]

4740

\[ {}2 y^{\prime }+a x = \sqrt {a^{2} x^{2}-4 b \,x^{2}-4 c y} \]

4741

\[ {}3 y^{\prime } = x +\sqrt {x^{2}-3 y} \]

4742

\[ {}x y^{\prime } = \sqrt {a^{2}-x^{2}} \]

4743

\[ {}x y^{\prime }+x +y = 0 \]

4744

\[ {}x y^{\prime }+x^{2}-y = 0 \]

4745

\[ {}x y^{\prime } = x^{3}-y \]

4746

\[ {}x y^{\prime } = 1+x^{3}+y \]

4747

\[ {}x y^{\prime } = x^{m}+y \]

4748

\[ {}x y^{\prime } = x \sin \left (x \right )-y \]

4749

\[ {}x y^{\prime } = x^{2} \sin \left (x \right )+y \]

4750

\[ {}x y^{\prime } = x^{n} \ln \left (x \right )-y \]

4751

\[ {}x y^{\prime } = \sin \left (x \right )-2 y \]

4752

\[ {}x y^{\prime } = a y \]

4753

\[ {}x y^{\prime } = 1+x +a y \]

4754

\[ {}x y^{\prime } = a x +b y \]

4755

\[ {}x y^{\prime } = a \,x^{2}+b y \]

4756

\[ {}x y^{\prime } = a +b \,x^{n}+c y \]

4757

\[ {}x y^{\prime }+2+\left (3-x \right ) y = 0 \]

4758

\[ {}x y^{\prime }+x +\left (a x +2\right ) y = 0 \]

4759

\[ {}x y^{\prime }+\left (b x +a \right ) y = 0 \]

4760

\[ {}x y^{\prime } = x^{3}+\left (-2 x^{2}+1\right ) y \]

4761

\[ {}x y^{\prime } = a x -\left (-b \,x^{2}+1\right ) y \]

4762

\[ {}x y^{\prime }+x +\left (-a \,x^{2}+2\right ) y = 0 \]

4763

\[ {}x y^{\prime }+x^{2}+y^{2} = 0 \]

4764

\[ {}x y^{\prime } = x^{2}+y \left (1+y\right ) \]

4765

\[ {}x y^{\prime }-y+y^{2} = x^{{2}/{3}} \]

4766

\[ {}x y^{\prime } = a +b y^{2} \]

4767

\[ {}x y^{\prime } = a \,x^{2}+y+b y^{2} \]

4768

\[ {}x y^{\prime } = a \,x^{2 n}+\left (n +b y\right ) y \]

4769

\[ {}x y^{\prime } = a \,x^{n}+b y+c y^{2} \]

4770

\[ {}x y^{\prime } = k +a \,x^{n}+b y+c y^{2} \]

4771

\[ {}x y^{\prime }+a +x y^{2} = 0 \]

4772

\[ {}x y^{\prime }+\left (1-x y\right ) y = 0 \]

4773

\[ {}x y^{\prime } = \left (1-x y\right ) y \]

4774

\[ {}x y^{\prime } = \left (x y+1\right ) y \]

4775

\[ {}x y^{\prime } = a \,x^{3} \left (1-x y\right ) y \]

4776

\[ {}x y^{\prime } = x^{3}+\left (2 x^{2}+1\right ) y+x y^{2} \]

4777

\[ {}x y^{\prime } = y \left (2 x y+1\right ) \]

4778

\[ {}x y^{\prime }+b x +\left (2+a x y\right ) y = 0 \]

4779

\[ {}x y^{\prime }+\operatorname {a0} +\operatorname {a1} x +\left (\operatorname {a2} +\operatorname {a3} x y\right ) y = 0 \]

4780

\[ {}x y^{\prime }+a \,x^{2} y^{2}+2 y = b \]

4781

\[ {}x y^{\prime }+x^{m}+\frac {\left (n -m \right ) y}{2}+x^{n} y^{2} = 0 \]

4782

\[ {}x y^{\prime }+\left (a +b \,x^{n} y\right ) y = 0 \]

4783

\[ {}x y^{\prime } = a \,x^{m}-b y-c \,x^{n} y^{2} \]

4784

\[ {}x y^{\prime } = 2 x -y+a \,x^{n} \left (x -y\right )^{2} \]

4785

\[ {}x y^{\prime }+\left (1-a y \ln \left (x \right )\right ) y = 0 \]

4786

\[ {}x y^{\prime } = y+\left (x^{2}-y^{2}\right ) f \left (x \right ) \]

4787

\[ {}x y^{\prime } = y \left (1+y^{2}\right ) \]

4788

\[ {}x y^{\prime }+y \left (1-x y^{2}\right ) = 0 \]

4789

\[ {}x y^{\prime }+y = a \left (x^{2}+1\right ) y^{3} \]

4790

\[ {}x y^{\prime } = a y+b \left (x^{2}+1\right ) y^{3} \]

4791

\[ {}x y^{\prime }+2 y = a \,x^{2 k} y^{k} \]

4792

\[ {}x y^{\prime } = 4 y-4 \sqrt {y} \]

4793

\[ {}x y^{\prime }+2 y = \sqrt {1+y^{2}} \]